Respuesta :
Answer:
.Graph f(x) = 6x + 2 and g(x) = 6x - 4. Then describe the transformation from the graph of f(x) to the graph of g(x). у 6. 5. 4. 3. 2 . 0 1 A -3 -2 -1 3 2 -i - 5 4 5 6 -3 ### 5. -6
Step-by-step explanation:
.Graph f(x) = 6x + 2 and g(x) = 6x - 4. Then describe the transformation from the graph of f(x) to the graph of g(x). у 6. 5. 4. 3. 2 . 0 1 A -3 -2 -1 3 2 -i - 5 4 5 6 -3 ### 5. -6
The transformation from the graph of f(x) to the graph of g(x) is a vertical shift down by 6 units
The functions are given as:
[tex]f(x) = 6x + 2[/tex]
[tex]g(x) = 6x - 4[/tex]
Subtract function f(x) from g(x),
[tex]k = g(x) - f(x)[/tex]
This gives
[tex]k = 6x - 4 - 6x - 2[/tex]
Collect like terms
[tex]k = 6x- 6x - 4 - 2[/tex]
[tex]k = -6[/tex]
The above represents the unit of translation of function f(x) to g(x).
Hence, the transformation from the graph of f(x) to the graph of g(x) is a vertical shift down by 6 units
Read more about function transformation at:
https://brainly.com/question/1548871